TEAM ORIENTED LEADERSHIP: A NEW APPROACH TO MOTIVATE SALESPERSON - Sri Ayuni; Diah Ayu Kusumawati; Wasitowati Wasitowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study examines how to achieve sales performance through team oriented leadership and team work quality. Teamwork can run smoothly if in organization have a team-oriented leader. The sampling technique used snowball sampling with the selection of respondents using purposive sampling (non probability sampling). This study used a sample of 348 salespeople from the life insurance industry. The data was collected by distributing questionnaires and direct interviews with salespeople. The results showed that team-oriented leadership and teamwork can improve sales performance. Good and strong quality of teamwork can be achieved through team-oriented leadership. So that these two variables can jointly achieve the best performance in sales activities.